2022
DOI: 10.2106/jbjs.21.01029
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Revision After Hip Fracture Fixation Using DePuy Synthes Trochanteric Fixation Nail or Trochanteric Fixation Nail Advanced

Abstract: Background: Prior reports of the DePuy Synthes Trochanteric Fixation Nail Advanced (TFNA) revealed a potential mode of fatigue failure at the proximal screw aperture following fixation of extracapsular hip fractures. We sought to compare the revision risk between the TFNA and its prior-generation forebear, the Trochanteric Fixation Nail (TFN).Methods: A retrospective cohort study was performed using data from a U.S. integrated health-care system's hip fracture registry. The study sample comprised patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…This finding is in line with other papers that reported approximately 5% reoperations after IM nail use [16]. Goodnough et al reported a 1.8-1.9% revision rate, but the definition of revision in this paper was limited to operations "in which a component was removed and/or replaced" [9]. Our definition was broader and included any reoperation of the hip.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This finding is in line with other papers that reported approximately 5% reoperations after IM nail use [16]. Goodnough et al reported a 1.8-1.9% revision rate, but the definition of revision in this paper was limited to operations "in which a component was removed and/or replaced" [9]. Our definition was broader and included any reoperation of the hip.…”
Section: Discussionsupporting
confidence: 83%
“…This device is different from other marketed nails as it was designed with a smaller proximal diameter -to allow greater preservation of native bone-but also a far stronger material, to reduce risk of breakage. As expected, a recent study looking at rate of nail breakage from TFNA vs that of other devices revealed no difference, and a 7,979 patients study from the Kaiser healthcare system further confirmed this finding [8,9].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Only 2 studies accounted for censoring of patients due to death. 13,15 In contrast, the rate could potentially be lower than reported, such as if breakages were diagnosed when they did not occur (coding or documentation errors) or partial capture of patients at risk (missing patients that had the implants inserted).…”
Section: Discussionmentioning
confidence: 96%
“…[14][15][16] The fourth study detected revisions defined as any operation after index procedure in which a component was removed and/or replaced; however, it did not specify how the database was queried for that outcome. 13 Those patients then had a hospital record review.…”
Section: Detection Of Breakagementioning
confidence: 99%